FUNGSI CERITA RAKYATSABUK BIDADARI DALAM MASYARAKAT SUKU SASAK - Sultana Sultana; Rusdiawan Rusdiawan; Ida Bagus Kade Gunayasa (Center of Language and Cultural Studies, 2019)
This study explores the oral story of the Sasak tribe “The Angel Belt”. As a literary work, especially oral literature or Sasak stories this study posed that Sasak literary works not only function as an entertainment, or bedtime, but it leads to the low public aspiration of the region’s literature. The research questions of this study were what functions are identified in the folk tales of Angel Belt in Sasak society in Bujak village Batukliang sub-district? This research constituted a descriptive qualitative which described the existence of functions and seen in the story, behavior character, and motivation or action in the role of each character in a story. The analysis began with the determination of informants, data collection data analysis then draw a conclusion. The results show that in the story “Angel Belt” contained the function as follows: a) as a projection system, namely collective reflection tools, b) as a means of consolation, c) as an educational tool, d) as a tool of criticism.